HIGH-RISK AI SYSTEMS IN THE LIGHT OF THE REGULATION (EU) 2024/1689 OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL FROM THE PERSPECTIVE OF THE POTENTIAL HARMFUL IMPACT ON PERSONALITY RIGHTS - Matefi, Roxana (International Journal of Legal and Social Order, 2025)
This article aims to analyze artificial intelligence systems, classified by the newly adopted EU AI ACT as high-risk, with a focus on their potential to infringe on personal rights. The growing role of artificial intelligence seems to be increasingly shaping the times we live in, and its influence is becoming increasingly evident, both at the individual and societal levels. Its applications are increasingly varied, as are the users of these tools, and access to them is becoming easier. The initial resistance to implementing systems based on various forms of artificial intelligence seems to be diminishing as the benefits of using these systems become increasingly apparent, often relieving individuals of truly burdensome tasks. The use of artificial intelligence has become so widespread that it is difficult to find an area that has not yet been "contaminated" by the influence of AI.In this general context, one of the main issues that should concern us is the risks generated by the use of these systems, as well as the ways in which we can limit, if not eliminate, their potentially harmful effects. At European level, an extremely important step in this direction was taken with the adoption of the REGULATION (EU) 2024/1689 OF THE EUROPEAN PARLIAMENT AND OF THE COUNCIL of 13 June 2024 laying down harmonised rules on artificial intelligence and amending Regulations (EC) No 300/2008, (EU) No 167/2013, (EU) No 168/2013, (EU) 2018/858, (EU) 2018/1139 and (EU) 2019/2144 and Directives 2014/90/EU, (EU) 2016/797 and (EU) 2020/1828 (Artificial Intelligence Act), as we will refer to throughout the paper, regulation which, among other things, introduces a classification of artificial intelligence systems according to the degree of risk they may pose to the fundamental rights of individuals, providing a series of safeguards to reduce their harmful effects on these rights. The article will deal mainly with the high-risk systems and the mechanisms for reducing their harmful potential.